Pengaruh Pendekatan Concrete Pictorial Abstract (CPA) Terhadap Hasil Belajar Peserta Didik Pada Muatan Matematika di Kelas III SDN 110/1 Desa Tenam - mega widya ningrum; yantoro yantoro; Khoirunnisa Khoirunnisa (Jurnal Tunas Pendidikan, 2024)
This study aims to determine the effect of the Concrete Pictorial Abstract learning approach on student learning outcomes in Mathematics content in class III SDN 110/I Desa Tenam. This research was conducted in class III at SDN 110/I Tenam Village for the 2022/2023 academic year. This research is a quantitative study using quasi-experiments. The data was processed to compare the results of the pre-test and post-test in the experimental class and the control class. The results showed that learning Mathematics using the Concrete Pictorial Abstract approach for class III SDN 110/I Desa Tenam was more influential than using the conventional approach (teacher centered) in improve student learning outcomes. Based on the paired samples statistics test that has been carried out, a significance value of 0.000 (<0.05) is obtained, and the t-test with independent sample t test tcount > ttable (2.240 > 1.686). This shows that Ha is accepted and H0 is rejected, and there are differences in the learning outcomes of the CPA approach compared to the teacher centered approach. From the results of this study it is suggested that teachers use the CPA approach in providing learning concepts mathematics. Educators are expected to be able to provide teaching using concrete objects so that mathematics feels closer to the child's world. This is expected to have a positive influence in improving learning outcomes.